2006
DOI: 10.1097/01.aog.0000199950.64545.16
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Oral Contraceptives

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Any inconsistencies in reporting and pill use should have been distributed evenly between the groups, leading to a dilution of the effect and rejection of the hypothesis. Furthermore, our bleeding data were comparable to those reported in other studies of continuous OCP studies using a similar pill formulation, suggesting external validity to our findings [19,23]. Finally, changes in bleeding in the treatment group are unlikely to be related to the absorption of contraceptive steroid as pharmacokinetic studies have demonstrated that concomitant use of typical doses of doxycycline does not alter contraceptive steroid levels [25,26].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Any inconsistencies in reporting and pill use should have been distributed evenly between the groups, leading to a dilution of the effect and rejection of the hypothesis. Furthermore, our bleeding data were comparable to those reported in other studies of continuous OCP studies using a similar pill formulation, suggesting external validity to our findings [19,23]. Finally, changes in bleeding in the treatment group are unlikely to be related to the absorption of contraceptive steroid as pharmacokinetic studies have demonstrated that concomitant use of typical doses of doxycycline does not alter contraceptive steroid levels [25,26].…”
Section: Discussionsupporting
confidence: 88%
“…In a randomized study of continuous use of OCPs containing 20 mcg EE in combination with either 100 mcg of LNG or 1 mg Norethindrone acetate, the addition of 10 mcg EE to either regimen did not improve bleeding patterns [19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of ethinylestradiol, few patients require a pill containing more than 35 μg/d to prevent breakthrough bleeding. 87 Many clinicians advocate starting with the lowest ethinylestradiol dose to minimize risks. However, there are no data demonstrating that 10-to 20-μg/d ethinylestradiol doses are safer than 35 μg daily, and lower ethinylestradiol doses are associated with more unscheduled vaginal bleeding.…”
Section: Selecting a Contraceptive Pillmentioning
confidence: 99%
“… 67 In a different study, pills formulated with LNG had significantly less unscheduled bleeding than those formulated with norethindrone. 68 Additionally, discontinuation of the continuous CHC for 3 to 4 days in cases of bothersome unscheduled bleeding to allow for a withdrawal bleed is one option, as long as the discontinuation occurs after the first 21 days of use. 1 However, this technique is limited to once every 3 weeks, given the risk of decreasing contraceptive effectiveness.…”
Section: Combined Hormonal Contraceptivesmentioning
confidence: 99%